Analyzing The Impact On Gold Price Pre And Post Gst Implementation (Journal of Namibian Studies : History Politics Culture, 2023)
As compared to the previous, flawed, multi-taxation system, GST is seen as a significant improvement and is therefore seen as a tax reform in the country. Simultaneously, it assures clear and consistent taxation, controls the unorganized sector, improves logistics' effectiveness, and simplifies and reduces the complexity of administrative processes. The jewellery industry was predicted to see a significant impact from GST, although an adverse one. Initial reports indicated that jewelers would be required to pay a GST of 3% on gold items sold to consumers. All gold saw a drop in demand once GST was applied, which had an effect on its price. By comparing the pre- and post-GST trends in Gold prices and the market capitalization of the top 5 jewellery manufacturers, this study employed the paired sample T test to determine whether or not GST has had an effect on the jewellery industry. There are two time frames covered by this analysis: 14 days (for the short term) and 308 days (for the long term).